2013
DOI: 10.1021/jp408826f
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Gold Nanoparticles into 2D Arrays Induced by Bolaamphiphilic Ligands

Abstract: We performed synthesis and investigated the self-assembly properties of gold nanoparticles (NPs) with covalently attached bolaamphiphilic ligands (B-AuNPs). The judiciously designed coating rendered the NPs amphiphilic and induced their self-assembly. The B-AuNPs formed ordered two-dimensional structures over large areas upon simple drop-casting. The films exhibited an uncommon and applicable topography, consisting of densely packed rings of inner diameter of around 30 nm, with the B-AuNPs at the rim and an em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…The majority of studies of Langmuir films of fullerenes deal with chemically modified structures possessing hydrophilic anchors . In the case of gold nanoparticles (Au NPs), amphiphilicity was ensured by mixture of hydrophilic and hydrophobic capping ligands, which rearranged at the surface of nanoparticle core upon contact with water. …”
Section: Resultsmentioning
confidence: 99%
“…The majority of studies of Langmuir films of fullerenes deal with chemically modified structures possessing hydrophilic anchors . In the case of gold nanoparticles (Au NPs), amphiphilicity was ensured by mixture of hydrophilic and hydrophobic capping ligands, which rearranged at the surface of nanoparticle core upon contact with water. …”
Section: Resultsmentioning
confidence: 99%
“…A peculiar example of amphiphilic ligand for AuNPs is a bola-amphiphilic thiolate that covalently bounds to metallic nanoparticles, giving rise to spontaneous self-assembly in regular, complex structures made of ring-like domains [ 87 ]. These structures were found useful for technological development of nanostructured surfaces over macroscopic areas suitable for the integration of nanotechnology into commercial devices.…”
Section: Hydrophilic and Amphiphilic Ligands Capping Agents For Amentioning
confidence: 99%
“…Recent observations have shown that the type of particle assembly (2D or 3D) has a strong effect on collective properties. For example, pronounced IR transparency and electrical insulation were found for AuNPs assembled as a layer (2D), and a decrease in electrical resistance was found for AuNPs assembled in 3D [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%